The Influence of Rider Concentration, Vehicle Completeness and Traffic Discipline on Motorcycle Rider Safety - Dewa, Adenanthera (Research Horizon, 2023)
Transportation plays a crucial role in driving development, particularly in developing countries such as Indonesia. This study aims to analyze the concentration of riders, vehicle equipment, traffic discipline on the safety of motorcyclists on the lasem-rembang pantura road. In this study, researchers used two types of data, including Qualitative Data and Quantitative Data. The results show that rider concentration, vehicle completeness, and traffic discipline have a positive and significant influence on motorcyclist safety. The results of the simple regression test show that the three variables have a positive coefficient, which means that the higher the concentration, vehicle equipment, and traffic discipline, the higher the level of rider safety.